Preferences and agreement in legislative parties: testing the causal chain. Issue 1 (2nd January 2017) - Close, Caroline; Núñez, Lidia
ABSTRACT: This research note focuses on two specific dimensions of legislative cohesion: the homogeneity of preferences within a party and party agreement. Although these two dimensions have often been considered as synonyms, it is argued that these two concepts refer to different realities. The authors therefore develop distinct measurements for these two concepts. The authors then examine their statistical relationship, putting to the test the widespread assumption that heterogeneous preferences increase the probability of disagreement. The authors do so by testing the effect of different measures of a member of parliament's ideological distance to her/his party on her/his self-reported frequency of disagreement with her/his party. It is demonstrated that the causal chain linking both concepts is only verified in the case of a conscious ideological distance. The results have crucial theoretical and methodological implications for future research on party cohesion and party unity.